2017
DOI: 10.15547/bjvm.916
|View full text |Cite
|
Sign up to set email alerts
|

Study on the oxidative changes in milk lipids, induced by subclinical mastitis and different milking regimes in cows

Abstract: SummaryChipilev, N., G. Kalinova, H. Daskalov & A. Slavova, 2017. Study on the oxidative changes in milk lipids, induced by subclinical mastitis and different milking regimes in cows. Bulg. J. Vet. Med., 20, No 2,[161][162][163][164][165][166][167][168] The fatty acid composition, the amount of free fatty acids and primary and secondary products of oxidation were investigated in relation to quality of raw cows milk produced and stored at a farm with a central milk duct. Raw milk samples were collected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Redox systems in milk are presented by the leukoriboflavin/riboflavin couple, cysteine/cystine couple, and ascorbic acid/dehydroascorbic acid couple . Chipilev et al demonstrated that redox substances of milk are vital inhibitors of undesirable oxidative changes. The formation of the “oxidized” flavor of milk was shown to be a result of the action of “antioxidative” and “prooxidative” factors …”
Section: Redox Interactions In Foodstuffsmentioning
confidence: 99%
See 3 more Smart Citations
“…Redox systems in milk are presented by the leukoriboflavin/riboflavin couple, cysteine/cystine couple, and ascorbic acid/dehydroascorbic acid couple . Chipilev et al demonstrated that redox substances of milk are vital inhibitors of undesirable oxidative changes. The formation of the “oxidized” flavor of milk was shown to be a result of the action of “antioxidative” and “prooxidative” factors …”
Section: Redox Interactions In Foodstuffsmentioning
confidence: 99%
“…The formation of the “oxidized” flavor of milk was shown to be a result of the action of “antioxidative” and “prooxidative” factors Adding pro-oxidants (redox mechanism) resulted in the reduction of the total antioxidant capacity of milk and an increase in products of oxidation . Therefore, reduction processes in unpasteurized milk should be considered as quality improving factors.…”
Section: Redox Interactions In Foodstuffsmentioning
confidence: 99%
See 2 more Smart Citations
“…Verma;Ambatipudi (2016) showed that modified gas chromatography and mass spectrometry might be effective for determining free fatty acid, polyunsaturated fatty acid, and prostaglandin levels in the mastitis-affected cow milk. Chipilev et al (2017) reported chromatographic and spectrophotometric methods for the detection of fatty acid peroxidation in bovine milk.…”
Section: Zincmentioning
confidence: 99%